Persepsi Peserta Didik Tentang Fungsi Komunikasi Guru BK dalam Menyelenggarakan Pelayanan Bimbingan dan Konseling - Mardelis, Weni - (Bimbingan dan Konseling, 2014)
This research is motivated by the implementation of the communication function is not wellby teachers BK so that guidance and counseling services have not been going well. BK teachers cannot create intimate communication with others, especially with friends profession, yet skilledcounseling teacher communicates in organizing guidance and counseling services and BK yet lessskilled teachers communicate with learners. This research is descriptive quantitative. Sampling wasdone using stratified random sampling technique. This study took a sample of students who serve asthe primary respondents numbering 81 people. The instrument used in this study was a questionnaire.As for the use of data analysis techniques percentage. The results of this study revealed that: BKteacher competence in communicating in organizing guidance and counseling services in terms ofinformation, dissemination and reactions are mostly located in the unfavorable category.